The Effect of the Tau Protein on D. melanogaster Lifespan Depends on GSK3 Expression and Sex. - Veselkina, E.R.; Trostnikov, M.V.; Roshina, N.V.; Pasyukova, E.G. (International journal of molecular sciences, 2023)
The microtubule-associated conserved protein tau has attracted significant attention because of its essential role in the formation of pathological changes in the nervous system, which can reduce longevity. The study of the effects caused by tau dysfunction and the molecular mechanisms underlying them is complicated because different forms of tau exist in humans and model organisms, and the changes in protein expression can be multidirectional. In this article, we show that an increase in the expression of the main isoform of the Drosophila melanogaster tau protein in the nervous system has differing effects on lifespan depending on the sex of individuals but has no effect on the properties of the nervous system, in particular, the synaptic activity and distribution of another microtubule-associated protein, Futsch, in neuromuscular junctions. Reduced expression of tau in the nervous system does not affect the lifespan of wild-type flies, but it does increase the lifespan dramatically shortened by overexpression of the shaggy gene encoding the GSK3 (Glycogen Synthase Kinase 3) protein kinase, which is one of the key regulators of tau phosphorylation levels. This effect is accompanied by the normalization of the Futsch protein distribution impaired by shaggy overexpression. The results presented in this article demonstrate that multidirectional changes in tau expression can lead to effects that depend on the sex of individuals and the expression level of GSK3.